Survey of Inhibiting Factors of Curriculum at SMK Telkom 1 Medan - Thoip Nasution, Putra; Haura, Affiyah; Mutia Asmara, Devi Sunita; Azmi, Nurul; Nurul Amin, Nusaindah; Rahmasari, Rahmasari (Pedagogik: Jurnal Pendidikan dan Riset, 2025)
This article was created to analyze the inhibiting factors of curriculum in SMK, while the things that will be discussed in this study are: 1). What is the curriculum applied in the school? 2). Does learning go according to the existing curriculum? 3). What are the complaints in learning about the use of the current curriculum?The research method used in the making of this article are qualitative method. The data was collected by analyzing material sources from books, journals, and take the questioners of some seconds grade students in SMK by using google form to know their answer about the inhibiting factors of curriculum they use in their school namely SMK Telkom 1 Medan.